JENIS â JENIS KAPANG PENGKONTAMINASI KOPI BUBUK DARI BEBERAPA PASAR TRADISIONAL DI KABUPATEN PASAMAN - Siregar, Nur Asiah; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACTGround coffee processed products sold in traditional markets in district of Pasaman seen from the processing and marketing that still traditional, because the ground coffee is not packaged in plastic and not branded. Ground coffee sold in an open container, so that the ground coffee directly exposed to the air. This case could lead to contamination of ground coffee is marketed by microorganisms especially fungi carried by air. This research aims to determine the types of mold found in coffee powder of several traditional markets in district of Pasaman. The research was conducted at the FMIPA Microbiology Laboratory, Andalas University from July until August 2013. This research uses purposive sampling method by selecting a place or market sampling by certain characteristics. The result in the identification using reference book Samson and Hoekstra (1988) subsequently described. The Samples were taken by 5 types of ground coffee samples from different manufacturers as well as traders. The results of this research showed that the samples of ground coffee found 7 types of A. niger, A. flavus, A. ustus, A. ochraceus, A. oryzae, Aspergillus sp 1 (suspected Aspergillus fumigatus), and Aspergillus sp 2. Penicillium genus there are 2 types of Penicillium glabrum and Penicillium sp. (allegedly Penicillium citrinum). There is only one genus Mucor Mucor hiemalis type. Rhizopus genus there is only 1 type of the Rhizopus oryzae. Genus Syncephalastrum there is 1 type that is Syncephalastrum racemosum.Â